2011
DOI: 10.1143/jpsj.80.034708
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Field-Induced Transitions in Spinel GeCo2O4

Abstract: The spinel GeCo 2 O 4 has the pyrochlore lattice of Co 2þ ions, in which the kagomé and triangular planes stack alternately along the [111] direction. It shows antiferromagnetic ordering below T N $ 21 K with a characteristic wave vector of Q M ¼ ð1=2; 1=2; 1=2Þ. The spin arrangement is ferromagnetic in the kagomé and triangular planes and antiferromagnetic between the kagomé planes as well as between the triangular planes. GeCo 2 O 4 exhibits a magnetic phase transition at H $ 4 T. Powder neutron diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 17 publications
3
20
0
Order By: Relevance
“…The amplitude of this component decreases from 3.1 to 1.8 µ B between 5.5 and 9.4 T while the FM component increases. On the TRI site, the AFM component is found equal to zero above H c1 , as already proposed [10]. At µ 0 H=12 T, i.e.…”
Section: A Magnetic Structure In Zero and Finite Magnetic Fieldssupporting
confidence: 84%
See 1 more Smart Citation
“…The amplitude of this component decreases from 3.1 to 1.8 µ B between 5.5 and 9.4 T while the FM component increases. On the TRI site, the AFM component is found equal to zero above H c1 , as already proposed [10]. At µ 0 H=12 T, i.e.…”
Section: A Magnetic Structure In Zero and Finite Magnetic Fieldssupporting
confidence: 84%
“…Their microscopic origin was investigated by powder neutron diffraction under magnetic field up to 10 T [10]. A transition, observed at ≈ 4 T, was attributed to an antiferromagnetic-toferromagnetic spin rearrangement between the triangular planes while retaining the antiferromagnetic arrangement arXiv:1609.08805v2 [cond-mat.str-el] 25 Jan 2017 at µ0H=0 T for the k1 domain (one of the 3 equipopulated S-domains represented) (a), at µ0H=5.5 T for the k1 domain (b) and at µ0H=12 T for the k3 domain after the high-field spin-reorientation (c).…”
Section: Introductionmentioning
confidence: 99%
“…An appreciable feature can be clearly observed: the intensity of the (1/2 1/2 1/2) Bragg peak is significantly enhanced, while the intensity of the (3/2 1/2 1/2) Bragg peak is drastically suppressed. A similar feature was observed previously in polycrystalline GeCo2O4 sample, which was ascribed to a combination of magnetic domain reorientation and a change of magnetic structure with either spins in neighboring triangular planes or spins in both neighboring triangular and Kagome planes turned into ferromagnetic alignment[21]. Nevertheless, distinct from GeCo2O4 where the nuclear Bragg peak intensity is also enhanced due to the fieldinduced canted ferromagnetic moment, no increase in nuclear Bragg peak intensity is observed in GeNi2O4 at 6 T, suggesting negligible ferromagnetic spin component at high field in either Kagome or triangular planes.The temperature dependence of both (1/2 1/2 1/2) and (3/2 1/2 1/2) magnetic Bragg peak intensities measured at H = 7 T on CG4C is shown in Fig.5(b).…”
supporting
confidence: 85%
“…By simply comparing the ratio of TN/θW, both GeTM2O4 compounds should not be regarded as highly frustrated magnets, where the magnetic frustration arises due to the competition of magnetic interactions between neighboring spins and further neighbors [13]. Neutron diffraction studies have shown that the ground state spin structure of these two compounds are similar, with a single ordering k-vector of (1/2 1/2 1/2), both having spins within the Kagome (triangular) planes ferromagnetically coupled whereas spins between the adjacent Kagome (triangular) planes being antiferromagnetically coupled [8,13,20,21]. On the other hand, in contrast to GeCo2O4 in which spins in Kagome and triangular lattices order simultaneously at TN and have the same moment size, for GeNi2O4 spins in the Kagome planes partially order at TN2 < T < TN1 but spins in the triangular planes remain completely disordered, which is followed by the ordering of spins in the latter planes at T < TN2 [8,13,18,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation